The Influence of Time Balance and Involvement Balance on Job Satisfaction among Employees of PLTU PT Bakti Nugraha Yuda Energy in Baturaja, OKU Regency - Dicky Roy; Munajat; Rini Efrianti (Cita konsultindo, 2026)
PT Bakti Nugraha Yuda Energy is a steam power plant (PLTU) company located in Baturaja, OKU Regency. Time balance and involvement balance represent an individual's ability to fulfill professional commitments while managing family responsibilities and other non-work obligations. This study aims to analyze the influence of time balance and involvement balance on job satisfaction using multiple linear regression as the data processing method. The results indicate that, both simultaneously and partially, time balance and involvement balance significantly influence the job satisfaction of employees at PLTU PT Bakti Nugraha Yuda Energy.